2015
DOI: 10.3390/rs70607181
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Comparison of High-Resolution Satellite Precipitation Products over Central Asia

Abstract: This paper examines the spatial error structures of eight precipitation estimates derived from four different satellite retrieval algorithms including TRMM Multi-satellite Precipitation Analysis (TMPA), Climate Prediction Center morphing technique (CMORPH), Global Satellite Mapping of Precipitation (GSMaP) and Precipitation Estimation from Remotely Sensed Information using Artificial Neural Networks (PERSIANN). All the original satellite and bias-corrected products of each algorithm (3B42RTV7 and 3B42V7, CMORP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
109
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(114 citation statements)
references
References 93 publications
(104 reference statements)
5
109
0
Order By: Relevance
“…Guo et al, 2015;Blacutt et al, 2015;Ward et al, 2011;Scheel et al, 2011). Here, we further subdivide daily rainfall in five types of events, which are used to classify precipitation based on its daily intensity, ranging from no rain (dry day; < 1 mm d −1 ) to violent rain (> 40 mm d −1 ), as shown in Table 2.…”
Section: Performance Indicesmentioning
confidence: 99%
“…Guo et al, 2015;Blacutt et al, 2015;Ward et al, 2011;Scheel et al, 2011). Here, we further subdivide daily rainfall in five types of events, which are used to classify precipitation based on its daily intensity, ranging from no rain (dry day; < 1 mm d −1 ) to violent rain (> 40 mm d −1 ), as shown in Table 2.…”
Section: Performance Indicesmentioning
confidence: 99%
“…The PDF is the proportion of the number of times that rainfall events from each bin occurs divided by the total number of rainfall events. To considering the rainfall intensity (R), this study has divided rainfall into eight bins [20]: (1) no rain (R = 0), (2) 0 < R ≤ 0.5 mm/day, (3) 0.5 mm/day < R ≤ 1 mm/day, (4) 1 mm/day < R ≤ 2 mm/day, (5) 2 mm/day < R ≤5 mm/day, (6) 5 mm/day < R ≤ 10 mm/day, (7) 10 mm/day< R ≤ 20 mm/day and (8) R > 20 mm/day. The pixels nearest the gauge stations were selected to calculate the rainfall intensities.…”
Section: Probability Distribution and Contingency Statisticsmentioning
confidence: 99%
“…For example, Hirpa et al evaluated the accuracies of three products (CMORPH, PERSIANN and TRMM3BV42) and found that both CMORPH and TRMM underestimated precipitation over higher elevations [19]. Guo Hao et al evaluated four products (TRMM, CMORPH, PERSIANN, GSMaP) using in situ measurements over Central Asia from 2004 to 2006 and most of the products overestimated the precipitation [20]. Awange et al used a "three-cornered-hat" method to assess six precipitation products and indicated that the RG-merged products had higher accuracies than the satellite-only products [21].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, pixels located closer than 27 km or farther than 185 km from the radar or behind the hilly region are excluded due to insufficient reliability of the radar data, and pixels located in proximity of major lakes are excluded due to false rainfall signals in the CMORPH estimates (e.g. Guo et al, 2015). The number of pixels analysed for each climatic region is reported in Table 1.…”
Section: Comparison Between Intensity-duration-frequency Mapsmentioning
confidence: 99%